2015
DOI: 10.1007/s10482-015-0636-7
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus phylogeny reveals an association of agriculturally important Fusarium solani species complex (FSSC) 11, and clinically important FSSC 5 and FSSC 3 + 4 with soybean roots in the north central United States

Abstract: The Fusarium solani species complex (FSSC) includes important root pathogens of soybean in the United States, but the evolutionary lineages associated with soybean root rot are unknown. A multilocus phylogeny based on 93 isolates from soybean and pea roots from North Dakota and Minnesota revealed that root rot was associated with three known phylogenetic species, FSSC 3 + 4 (=Fusarium falciforme) (3 % of isolates), FSSC 5 (60 %), FSSC 11 (34 %), and one unknown species, FSSC X (2 %). Of these species FSSC 5 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Notes -Diverse studies suggested that the different taxa here reduced to synonymy under N. phaseoli differ by biogeographical patterns, pathogenicity and morphology (Aoki et al 2003, 2012a, b, O'Donnell et al 2010. These variations are not mirrored in genus-wide phylogenetic studies using markers traditionally employed for this genus (Nalim et al 2011, Chitrampalam & Nelson 2016, Costa et al 2016, Dallé Rosa et al 2018. The phylogenetic results here showed that an internal phylogenetic structure does exist within the N. phaseoli clade (Fig.…”
Section: Neocosmospora Perseaementioning
confidence: 99%
See 1 more Smart Citation
“…Notes -Diverse studies suggested that the different taxa here reduced to synonymy under N. phaseoli differ by biogeographical patterns, pathogenicity and morphology (Aoki et al 2003, 2012a, b, O'Donnell et al 2010. These variations are not mirrored in genus-wide phylogenetic studies using markers traditionally employed for this genus (Nalim et al 2011, Chitrampalam & Nelson 2016, Costa et al 2016, Dallé Rosa et al 2018. The phylogenetic results here showed that an internal phylogenetic structure does exist within the N. phaseoli clade (Fig.…”
Section: Neocosmospora Perseaementioning
confidence: 99%
“…Members of Neocosmospora (as the FSSC) have been traditionally classified in the asexual genus Fusarium, and characterised based on morphological features of the asexual morph, pathogenicity on specific hosts, and sexual or asexual compati bility (Matuo & Snyder 1973, Chitrampalam & Nelson 2016). However, the many different taxonomic schemes applied to this fungal group have led to a confused application of names as well as obscure synonymies.…”
Section: Species Concepts In Neocosmospora the Asexual-morph Dilemmamentioning
confidence: 99%
“…In a recent study, Fusarium sp. (FSSC 5)and F. falciforme(FSSC 3 + 4)were isolated from soybean roots 50) . In a case of Fusarium keratitis outbreak associated with contact lens use in the United States between 2004 and 2005, OʼDonnell et al concluded that patientsʼ bathroom sink drains represented a likely source of Fusarium infection 51) .…”
Section: )mentioning
confidence: 99%
“…A first phylogenetic analysis was carried out using RPB2 sequences in order to assess the isolate distribution on the different species complexes of Fusarium and fusarium-like genera. To establish the identity of the isolates to the species level, different phylogenetic analyses were conducted first individually for each locus and then as multilocus sequence analyses using the following loci combinations: CAM , EF-1α , ITS, RPB1 , RPB2 and TUB for members of the Fusarium fujikuroi species complex (FFSC) ( O’Donnell et al 2000 , Edwards et al 2016 ); RPB1 , RPB2 and TUB , for members of the Fusarium lateritium species complex (FLSC); EF-1α , ITS, LSU, RPB1 and RPB2 for isolates related with the Fusarium tricinctum species complex (FTSC); and lastly EF-1α , ITS, LSU and RPB2 for isolates belonging to Neocosmospora (formerly known as the Fusarium solani species complex, FSSC) ( O’Donnell et al 2008 , Lombard et al 2015 , Chitrampalam & Nelson 2016 ). Isolates belonging to the FOSC were characterised based on their haplotype distribution using a two-locus dataset that included EF-1α and IGS sequences following the procedures and alignments of O’Donnell et al (2009a) .…”
Section: Methodsmentioning
confidence: 99%